TRADISI SEDEKAH BUMI DALAM PELESTARIAN BUDAYA LOKAL DI DUSUN WONOSARI DESA TEBANG KACANG - Lestari, Evi Dwi; Noor, Agus Sastrawan; Firmansyah, Andang (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe problems raised in this study are summarized in three formulations of the problem, namely, regarding the background, procedures and rituals and how the involvement of community members in preserving the meaning of Sedekah Bumi tradition in Wonosari, Tebang Kacang Village, Sungai Raya District, Kubu Raya Regency. To achieve the objectives of the study the researcher used qualitative methods. The data collection techniques with observation, interviews, and documentation. The results of this study indicate that Sedekah Bumi tradition in Wonosari, Tebang Kacang Village, against the arrival of Javanese people to Wonosari. They mean that, Tebang Kacang is human form of gratitude and to get a better life the following year. Sedekah Bumi held at the turn of the Islamic New Year or the Hijriah New Year. Regarding the ceremonial procedures and rituals, it is divided into three stages, namely, cattle slaughter, festivity and salvation, and wayang performances. All communities participate in this event. They are very supportive of the big activities held once a year in Wonosari, Tebang Kacang Village. Based on the results of the study, the researcher concluded that Sedekah Bumi held once a year on the eve of the Hijriah New Year by involving all elements of the community at each stage of the ceremony. Keywords: Tradition, Local Culture, Islamic New Year